Tax non-compliance of small and medium-sized corporations (SMCs) and tax auditors’ aggressiveness in judgment when auditing SMCs / Nor Azrina Mohd Yusof@Ghani - Mohd Yusof@Ghani, Nor Azrina (Institute of Graduate Studies, UiTM, 2016)
The pervasiveness of tax non-compliance remains a serious concern to most tax authorities around the world. The loss of tax revenue due to tax noncompliance has prompted tax authorities to strengthen their tax audit and tax investigation. In Malaysia, although tax authorities have initiated tax audit regularly and impose tax penalties, the issue of tax non-compliance among small-and medium-sized corporations (SMCs) still persist. The unresolved issue signals the question as to whether the increase in tax noncompliance is due to the tax auditors’ aggressiveness in judgment when auditing SMCs. The importance of understanding tax non-compliance as well as tax auditors’ aggressiveness in judgment, couple with the lack of empirical research is the motivation of this study. The first objective is to examine the determinants of tax non-compliance of SMCs. This study analysed archival tax data obtained from the Corporate Tax Department, IRBM, located at Duta Street, Kuala Lumpur. A total of 513 audited and resolved corporate tax cases in 2011 were obtained. Of these 513 tax cases, 286 are non-compliant SMCs. The findings show RM31.3 million additional taxes and penalties were collected from these non-compliant SMCs. The hierarchical multiple regression was used to test the proposed research model, which is formulated based on the economic deterrence theory. Out of six hypotheses, four hypotheses are supported whereby tax rate, foreign ownership, firm size and construction industry are found significantly related to tax non-compliance of SMCs. The most significant predictor is firm size followed by construction industry, tax rate and foreign ownership. The second objective is to test the tax auditors’ aggressiveness in judgment model based on culpability theory…